Effects of Progressive Muscle Relaxation on Academic Stress in Students - Arman Bin Anuar; Muhammad Anas; Sulaiman Samad (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2019)
This study aims to describe (1) the practice of progressive muscle relaxation (PMR) for academic stress in students; (2) the levels of students’ academic stress before and after the treatment of PMR; and (3) the effects of PMR on students’ academic stress. This quantitative-based study used a quasi-experimental design and a non-equivalent control groups design. The sample of the study was 40 students of the eleventh grade identified with high level of academic stress. Data were collected through observation and academic stress scale, analyzed using descriptive analysis technique and statistics analysis techniques with paired sample t-test and independent sample t-test. Results of the study show that (1) PMR was performed in accordance with the procedures; (2) students had high level of academic stress before performing PMR, but had low academic stress after performing PMR; and (3) PMR had a positive impact on students’ academic stress, meaning that it can be used to reduce academic stress in students.